2014
DOI: 10.1371/journal.pone.0109636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of A11 Neurons Projecting to the Spinal Cord of Mice

Abstract: The hypothalamic A11 region has been identified in several species including rats, mice, cats, monkeys, zebrafish, and humans as the primary source of descending dopamine (DA) to the spinal cord. It has been implicated in the control of pain, modulation of the spinal locomotor network, restless leg syndrome, and cataplexy, yet the A11 cell group remains an understudied dopaminergic (DAergic) nucleus within the brain. It is unclear whether A11 neurons in the mouse contain the full complement of enzymes consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 59 publications
(63 reference statements)
5
67
1
Order By: Relevance
“…Another group of DA neurons, located in the hypothalamus (A11), sends descending projections to the spinal cord in lamprey (41), zebrafish (42), mice (43), rats (44), and primates (45) (Fig. S3B)] was transiently evoked following PT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of DA neurons, located in the hypothalamus (A11), sends descending projections to the spinal cord in lamprey (41), zebrafish (42), mice (43), rats (44), and primates (45) (Fig. S3B)] was transiently evoked following PT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic posterior tuberculum/A11: In both fish and mammals these nuclei contain the only dopaminergic cell type that projects to the spinal cord (Tay et al, 2011; Koblinger et al, 2014), and are specified by the expression of common transcription factors (Löhr et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Note that a large number of intensely GAD-IR processes were observed in the hypothalamus (ventral) region including A11, and more weakly GAD-IR processes were present in the thalamus (dorsal). The delimited areas in a-c are shown at higher magnification in d- ◂ [2,4,5,33]. In these previous studies, it was also reported that there were projections to the spinal cord derived from both non-TH and TH neurons of the A11 region.…”
Section: Projection To the Spinal Cordmentioning
confidence: 77%
“…Dopaminergic neurons are enriched in several brain regions designated as A8-A16 [1]. Among these, the A11 dopaminergic system is the only dopaminergic system that gives rise to descending projections to the spinal cord [2,4,5]. In addition to these particular neural connections, the fact that dopaminergic receptors are present in the spinal cord, and that dopamine receptor agonists alleviate the symptoms of restless legs syndrome (RLS), led to the hypothesis that hypo-activity of A11 neurons is a contributing factor in the pathogenesis of RLS [3].…”
Section: Introductionmentioning
confidence: 99%